2023
DOI: 10.1111/sjtg.12499
|View full text |Cite
|
Sign up to set email alerts
|

‘Where there is fish, is where I put my head’: Challenges of mobile fishers in Elmina fishing community in Ghana

Abstract: Small‐scale fisheries are crucial for improving livelihoods by providing fisher employment, and food security. As part of their work, fishers frequently move to different fishing communities to catch and trade in fish. This paper analyses the living circumstances of artisanal fishers and discusses their mobility patterns, lodging arrangements, and the difficulties they encounter as they carry out their work. This paper is based on a study that involved 385 artisanal fishers in the fishing community of Elmina i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…This finding was predicted based on previous research confirming that female fishers are more knowledgeable about HIV testing and counselling services. Kyei‐Gyamfi (2023b) reported that the lesser mobility of female fishers allows for their greater participation in HIV interventions than their male counterparts, who often migrate between fishing settlements to catch fish.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was predicted based on previous research confirming that female fishers are more knowledgeable about HIV testing and counselling services. Kyei‐Gyamfi (2023b) reported that the lesser mobility of female fishers allows for their greater participation in HIV interventions than their male counterparts, who often migrate between fishing settlements to catch fish.…”
Section: Discussionmentioning
confidence: 99%